2010
DOI: 10.1111/j.1742-1241.2009.02227.x
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring treatment to the individual in type 2 diabetes practical guidance from theGlobal Partnership for Effective Diabetes Management

Abstract: Good glycaemic control continues to be the most effective therapeutic manoeuvre to reduce the risk of development and/or progression of microvascular disease, and therefore remains the cornerstone of diabetes management despite recent scepticism about tight glucose control strategies. The impact on macrovascular complications is still a matter of debate, and so glycaemic control strategies should be placed in the context of multifactorial intervention to address all cardiovascular risk factors. Approaches to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 27 publications
0
57
0
2
Order By: Relevance
“…7 The study duration of these trials (3.5-5.6 years) may have been too short for any significant benefits of tight glycaemic control on CV outcomes to become apparent (as opposed to the 10-year follow-up in the UKPDS). 16 Furthermore, the patients enrolled in the shortterm studies had a history of poorly controlled long-standing Table 1.…”
Section: Defining Glycaemic Targets: the Evidencementioning
confidence: 98%
See 3 more Smart Citations
“…7 The study duration of these trials (3.5-5.6 years) may have been too short for any significant benefits of tight glycaemic control on CV outcomes to become apparent (as opposed to the 10-year follow-up in the UKPDS). 16 Furthermore, the patients enrolled in the shortterm studies had a history of poorly controlled long-standing Table 1.…”
Section: Defining Glycaemic Targets: the Evidencementioning
confidence: 98%
“…diabetes together with either micro-or macrovascular complications, [13][14][15] and were therefore at higher risk of negative outcomes than their counterparts in the UKPDS (newly diagnosed patients with no prior CV events). 7 A meta-analysis of the UKPDS, Prospective Pioglitazone Clinical Trial in Macrovascular Events (PROactive), ADVANCE, ACCORD and VADT studies found that intensive therapy achieving a modest 0.9% (10 mmol/mol) reduction in HbA 1c was associated with a 17% reduction in non-fatal MI and a 15% reduction in coronary heart disease (CHD) compared with conventional therapy. 17 Further meta-analyses have also evaluated the effectiveness of good glycaemic control in preventing or delaying the onset of macrovascular complications and provide potential explanations for the lack of apparent benefits seen in landmark trials.…”
Section: Defining Glycaemic Targets: the Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Although the benefits of intensive and early glycemic control are well-documented [20,21], current management of glycemia is suboptimal and not enough people achieve their glucose targets [22]. In fact, as few as 25% of patients achieve their blood glucose goals in some T2DM populations [23] while an analysis from the USA showed that 35% of individuals were not reaching personalized goals [24].…”
Section: Introductionmentioning
confidence: 97%